Pengaruh Gaya Hidup, Promosi dan Keamanan Transaksi terhadap Keputusan Penggunaan Dompet Digital pada Generasi Z di Kabupaten Tabanan - Putra, Galang Pratama; Julianto, I Putu (Vokasi : Jurnal Riset Akuntansi, 2021)
Abstract This study aims to examine the effect of lifestyle, promotion, and transaction security on the decision to use digital wallets in generation Z in the Tabanan Regency area. The research design used in this study used quantitative methods. The subjects in this study were Generation Z in Tabanan Regency, aged 20-24 years in 2022, and the objects in this study were lifestyle, promotion, transaction security and decisions to use digital wallets. The total population used is 395 respondents. The instrument used in data collection is a questionnaire, and the data analysis technique used is multiple linear regression analysis with the help of the SPSS 25 program. The results of this study are (1) Lifestyle has an influence on decisions to use digital wallets. (2) Promotion has an influence on the decision to use digital wallets. And (3) Transaction Security has an influence on the decision to use digital wallets. Keywords: lifestyle, promotion, transaction security, decision to use digital wallet